Utilization of Microcontroller Technology as A Food and Beverage Menu Ordering for Service at The Cafe - Ashari, Mohammad Ibrahim; Artiyani, Anis (IJISTECH (International Journal of Information System and Technology), 2023)
The cafe service system in this modern era still uses manual labor. This is less effective in terms of service speed and of course will increase operational costs due to the need for a large number of waiters. For this reason, an electronic food and beverage ordering device is needed. This is useful for speeding up the service process and also reducing service personnel, of course, also reducing operational costs. This research will present the use of the ESP 8266 module as a minimum system design for ordering menus on consumer tables. Input from the dining table containing the menu code and number of menus will be displayed on the LCD. Furthermore, data will be sent from ESP 8266 to the kitchen to mix food and drinks ordered by consumers. The data is also transferred to the cashier's PC, whereupon the cashier prints invoices for consumers. From the test results on the LCD can already display a menu of food and drinks. The cashier PC and kitchen PC have also displayed the food and drink data ordered. Cashiers can also print bills for consumers.